ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KESEHATAN MENTAL IBU YANG MEMILIKI BALITA STUNTING - Marlina; Abdullah, Asnawi; Marthoenis; Hermansyah; Aramico, Basri (Jurnal Medikes (Media Informasi Kesehatan), 2025)
Mental health remains a global health challenge with significant impact. Mothers of stunted toddlers often experience psychosocial pressures that can negatively affect their mental well-being. In the working area of the Lampisang Community Health Center, cases of both stunting and mental health disorders remain prevalent. This study aims to analyze the factors associated with the mental health of mothers with stunted toddlers in this region. A quantitative research approach with a cross-sectional design was employed. The study was conducted from July 26 to August 1, 2024. The target population consisted of 725 mothers with toddlers. A proportional random sampling technique was used to select a total of 439 respondents. Inclusion criteria included mothers who had toddlers, lived within the Lampisang Community Health Center’s service area, and were willing to participate in the study. The exclusion criterion was mothers who were not present at the time of data collection. Logistic regression analysis was used to test the research hypothesis. The results showed that the most dominant factors associated with abnormal maternal mental health were the lack of support from husbands (OR = 72.94; CI = 23.78–223.71; p = 0.0001) and the incidence of stunting in toddlers (OR = 59.64; CI = 9.86–360.61; p = 0.0001). These findings indicate that lack of husband’s support and the presence of stunting in toddlers are the most significant contributors to mental health problems among mothers.